2017
DOI: 10.2174/1568009617666170330112842
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Discovery of Next Generation Reversible TMLR Inhibitors Targeting EGFR Activating and Drug Resistant T790M Mutants

Abstract: Next generation reversible inhibitors exhibited unique binding mode and were found to occupy three major pockets (ribose pocket, back pocket and hinge region), which is critical for increasing the selectivity of the compound against TMLR mutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Drug effect reversibility is an important factor in determining drug administration mode for optimizing efficacy and persistence while avoiding adverse secondary effects (20). The same drug may produce different effects on different types of tumor cells, mainly due to the particular cell type's genetic background (14).…”
Section: Discussionmentioning
confidence: 99%
“…Drug effect reversibility is an important factor in determining drug administration mode for optimizing efficacy and persistence while avoiding adverse secondary effects (20). The same drug may produce different effects on different types of tumor cells, mainly due to the particular cell type's genetic background (14).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was shown that Gln791/Glu762 acts as a hydrogen bond acceptor while interacting with the ligand. 32 Therefore, used the above structural features for defining the pharmacophore definition. As Met793 interaction showed an absolute 100% conservation, it was termed as “essential” constraint while interactions with either Gln791 or Glu762 was defined as “optimal”.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the resistance to T790M mutation and enable effective treatment, second‐ and third‐generation inhibitors were developed (Yadav, Singh, et al, 2014). These inhibitors covalently bind to cysteine 797 and inhibit mutant EGFR T790M; however, this produces side‐effects (Agarwal, Pal, Gupta, & Saini, 2017). Thus, in the last 7 years researchers have been synthesizing reversible non‐covalent inhibitors which are responsive to lung cancer (Agarwal et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These inhibitors covalently bind to cysteine 797 and inhibit mutant EGFR T790M; however, this produces side‐effects (Agarwal, Pal, Gupta, & Saini, 2017). Thus, in the last 7 years researchers have been synthesizing reversible non‐covalent inhibitors which are responsive to lung cancer (Agarwal et al., 2017).…”
Section: Introductionmentioning
confidence: 99%